PENGARUH PELAPORAN KEUANGAN MELALUI INTERNET DAN TATA KELOLA PADA KESULITAN KEUANGAN DI SEKTOR PERBANKAN - Permata Ayu Widyasari; Evelyn Christina Kurniawan (UNIB Press, 2020)
The research objective is to identify ownership structure, audit committee characteristics, and internet financial reporting impact on banking financial distress. Populations of this study are the banks registered in Indonesia Stock Exchange 2010-2018. This study use logistic regression method, which is done twice for the period 2010-2018 and the period 2018. The result shows a positive significant impact on audit committee financial literacy in is financial distress. The state ownership has a negative significant impact on financial distress for 2010-2018 data. This result is not supported by 2018 data, due to changes in government priority. Firm size as control variable has negative significant impact on financial distress. This research emphasizes that the practice of internet financial reporting need to be evaluated in banking sector.Keywords: Ownership Structure, Audit Committee Characteristic, Internet Financial Reporting, Financial Distress, Good Corporate Governance